The effect of paired associative stimulation with a high-intensity cortical component and a high-frequency peripheral component on heart rate and heart rate variability in healthy subjects - Haakana, P.; Holopainen, K.; Nätkynmäki, A.; Kirveskari, E.; Tarvainen, M. P.; Shulga, A. (Frontiers in Rehabilitation Sciences, 2023)
Objective: A novel protocol for paired associative stimulation (PAS), called high-PAS, consists of high-intensity transcranial magnetic stimulation (TMS) and high-frequency peripheral nerve stimulation (PNS). High-PAS was developed for spinal cord injury rehabilitation, and targets plastic changes in stimulated pathways in the corticospinal tract, which improves motor function. As therapy interventions can last many weeks, it is important to fully understand the effects of high-PAS, including its effect on cardiovascular system. Heart rate variability (HRV) has been used to measure changes in both sympathetic and parasympathetic systems. Methods: We used short-term HRV measurements to evaluate the effects of one 20-min session of high-PAS on 17 healthy individuals. HRV was recorded for 5 mins before (PRE), during (STIM), immediately after (POST), 30 mins after (POST30), and 60 mins after (POST60) the stimulation. Five participants repeated the HRV setup with sham stimulation. Results: As significant decrease in low-frequency (LF) power (n.u.) (p = 0.002), low-frequency to high-frequency (HF) ratio (p = 0.017), in Poincaré plot (the standard deviation of RR intervals perpendicular to (SD1) and along (SD2) the line of identity SD2/SD1 ratio p < 0.001), and increase in HF power (n.u.) (p = 0.002) were observed between PRE and STIM conditions; these changes were fully reversible immediately after stimulation. HR min decreased significantly from POST to PRE by 3% (p = 0.015) and continued to decline until POST60 by 5% (p = 0.011). LF power (ms2) (p = 0.017) and SD2 (p = 0.015) decreased from PRE to STIM and increased from PRE to POST (p = 0.025 and p = 0.017 respectively). Results from sham PAS exhibited a similar trend as active high-PAS stimulation. Conclusions: High-PAS does not have sustained effects during 60-min follow up on cardiovascular functions, as measured by HRV. None of the short-term results indicate activation of the sympathetic nervous system in healthy individuals. Observed changes in HRV indicate higher parasympathetic activity during stimulation, which is reversible and is plausibly explained by the fact that the participants spend 20 mins without moving, talking, or using phones while being stimulated.